Investment screening and venture capital - Vera Eichenauer; Stefan Köppl; Monika Köppl-Turyna (Kiel Institute for the World Economy (IfW Kiel), 2025)
In this paper we analyze the effects of investment screening on cross-border venture capital investments in Europe between 2007 and 2022. The data we work with is originally based on PRISM data which has been extended by Eichenauer and Wang and which we combine with deal data from Preqin to assess investment activity. Our results point to unintended negative effects: while the number of actually blocked deals has remained very low, the associated uncertainty and an increase in transaction costs have led to a significant decline in cross-border deals. The effects are stronger in the case of financial (i.e. "non-strategic") investors, for late-stage venture capital deals, and for deals with investors from non-OECD countries. Moreover, we observe changes in the size of deals and their structure. This has profound policy implications for the financing of innovation in Europe.
Keywords: F55; F21; G24; L14; 330; cross-border venture capital; investment screening; Europe; transaction costs